Public-private partnerships for infrastructure: Lessons learned from Dutch and Flemish PhD-theses - Hueskes, Marlies; Koppenjan, Joop; Verweij, Stefan (European Journal of Transport and Infrastructure Research, 2019)
In recent years, a considerable number of PhD-dissertations have appeared in the Netherland and Flanders (Belgium) on Public-Private Partnerships (PPPs) for the provision of public infrastructures such as transport infrastructure and public buildings. These PhD-theses provide valuable insights into how PPPs perform and especially into the conditions that influence their performance. We identified four clusters of relevant conditions: (1) public procurement procedures, (2) contract management, (3) transaction costs, and (4) democratic legitimacy and accountability. By discussing the theses in this article, their lessons learned become available for the international PPP-community. Our analysis of the PhD-theses shows that there are no definite arguments for or against the use of PPPs. The performance of PPP-arrangements depends on agency: on the skills and commitment of parties involved and on the way in which the arrangements are applied. The dissertations show that policymakers have to find ways to balance the need to reduce transaction costs through contract standardization with the need for tailor- made solutions in specific projects. Furthermore, the dissertations show that ‘soft’ contract management aspects, such as the quality of collaborative behavior and process management, are particularly important for the performance of PPPs. Finally, the theses bring to the fore the democratic issues involved in PPPs, showing their mixed results in terms of legitimacy and accountability.